A deletion hampering appropriate typing of Mycobacterium africanum. (March 2017) - Abascal, Estefanía; Herrera, Diana Maricela; Herranz, Marta; Santantón, Sheila; Martínez-Lirola, Miguel; Tudó, Griselda; Gonzalez, Juliá; Bouza, Emilio; Pérez-Lago, Laura; García-de-Viedma, Darío
Abstract: Molecular epidemiology analysis of tuberculosis transmission is based mostly on the application of MIRU-VNTR. In certain isolates a complete 24-loci genotype is not obtained and these incompletely genotyped isolates can not be used in the definition of clusters. In a population-based molecular epidemiology study performed in Almería, Southeast Spain, a context with a high proportion of immigrants, we found that an 88-bp deletion in isolates of Mycobacterium africanum Lineage 5 hampers MIRU-VNTR analysis. A more extensive analysis revealed that this deletion was shared by all the Lineage 5 isolates in certain countries of origin of immigrants, such as Equatorial Guinea, and is likely present in several other African countries and also in the USA. A procedure is proposed to enable epidemiological analysis of these isolates.